Extent of Demonstration Method on Mathematics Teaching Approaches Among Senior High School Students of Mindanao State University–Sulu - Annong-Aksan, Jainalyn (Journal of Interdisciplinary Perspectives, 2024)
The demonstration method is a vital teaching tool that helps students improve their procedural knowledge through observation, imitation, and technique adaptation in solving math problems. Employing this method with different approaches can enhance students' active learning, making it even more effective for mathematics teachers to address the issue of students' low academic performance in Mathematics. This study assessed the extent of the demonstration method on mathematics teaching approaches among senior high school students of Mindanao State University–Sulu. It employed a descriptive-correlational research design with 190 student respondents selected through a stratified random sampling method. The study reveals that, among the 190 student-respondents, mainly female and aged 17-18 in grade 11, with parents having a high school education, the demonstration method is viewed positively in math teaching. While the sample represents typical senior high school students, the lack of diversity in parental education may limit generalizability. Student perceptions vary by age and grade level, with older students preferring the teacher-centered approach, and grade 12 students showing overall positive views. The study highlights the consistent effectiveness of the demonstration method across teaching approaches, underscoring the importance of efficient implementation for student perceptions. The study recommends that school heads support teachers with resources, training, and feedback, monitor the method's effectiveness on student performance, and encourage the use of the demonstration method in mathematics teaching. Parents should be informed and involved in their children's learning, while students should actively engage in the demonstration method. Future research should explore the impact of parental education on student performance and investigate the effectiveness of the demonstration method in mathematics teaching.